THE EFFECT OF KNOWLEDGE MANAGEMENT AND SKILLS ON EMPLOYEE PERFORMANCE WITH ATTITUDE AS A MODERATING VARIABLE (STUDY AT PT. PERKEBUNAN NUSANTARA IV MEDAN) - Harahap, Putri Insani (Simangunsong : Journal of Business Administration, Management, Economic And Accounting, 2025)
PT. Perkebunan Nusantara IV Medan strives to focus on improving management knowledge, skills of its employees and creating good attitudes among its employees so that they work with high performance, quality, and with a large quantity of work. This will lead to the progress of PT. Perkebunan Nusantara IV Medan as one of the proud business units of the plantation community in North Sumatra. The skills they have are actually quite good, but due to the lack of willingness to continue learning, many employees are left behind by workers from private estates who continue to train themselves to be able to compete globally. As well as the attitude held by employees who consider that working at PTPN is more than and being indifferent to the conditions of the company. The purpose of this research is to find out and analyze whether knowledge management and skills influence the performance of employees partially and simultaneously at PT. Perkebunan Nusantara IV Medan and to know and analyze whether attitude moderates the effect of knowledge management and skills on employee performance at PT. Perkebunan Nusantara IV Medan. The number of samples in this study were 253 people using the Slovin technique. The analysis technique used is multiple linear regression and MRA. The results of the study show that knowledge management influences employee performance, skills affect employee performance and knowledge management and skills influence employee performance.Attitude gives the effect of weakening the influence of knowledge management on employee performance. Attitude gives the effect of weakening the influence of skills on employee performance